On the Intermittent Occurrence of Open‐Ocean Polynyas in a Multi‐Century High‐Resolution Preindustrial Earth System Model Simulation. Issue 4 (4th April 2022) - Diao, Xiliang; Stössel, Achim; Chang, Ping; Danabasoglu, Gokhan; Yeager, Stephen G.; Gopal, Abishek; Wang, Hong; Zhang, Shaoqing
Abstract: A 500‐year‐long high‐resolution Community Earth System Model simulation under preindustrial radiative forcing produces Maud Rise Polynyas (MRPs) and Weddell Sea Polynya (WSP) events intermittently from decadal (MRP) to multidecadal (WSP) timescales. This periodicity is correlated with the variation of a regional Southern Annular Mode (SAM) index (evaluated regionally instead of circum‐Antarctic) with corresponding variations of precipitation and winds over the Weddell Sea. A negative index causes the upper‐ocean salinity to increase over multiple decades. Ultimately, brine rejection during seasonal sea‐ice formation superimposed on the multidecadal increase raises the upper‐ocean salinity beyond the tipping point for triggering deep convection that leads to polynyas. The initiation of polynya events is thus controlled by surface properties while the location of initiation is determined by bathymetric features. The persistent Taylor column effect, which is well represented by the high‐resolution model topography of the Maud Rise seamount, preconditions this region for MRP initiation. Therefore, MRPs form more frequently than WSPs in the simulation. When the upper‐ocean salinity is high, deep convection in the MRP region tends to be stronger, in which case MRPs are also more likely to grow into WSPs. Once WSPs emerge, they affect the regional atmospheric circulation and associated variables. We propose a regional coupled ocean‐atmosphere mechanism to explain both the periodic emergence of polynyas and the periodic variation of the regional SAM index. Although the temperature and salinity of Weddell Deep Water show upward trends due to model drift, these density‐compensating changes do not affect the frequency of polynya formation. Plain Language Summary: Regions of open water surrounded by frozen sea water (sea ice) in winter are generally referred to as open‐ocean polynyas. A large version of such polynya has last been observed in the Weddell Sea in the mid 1970s. Such large polynyas play an important role for the global ocean circulation because they allow for vigorous exchange of heat between the atmosphere and the ocean. This process is associated with deep vertical overturning of the ocean, thus contributing significantly to the ventilation of the deep ocean. Many low‐resolution Earth System Models simulate open‐ocean polynyas in the Weddell Sea, but presumably for the wrong physical reasons. Based on a 500‐year‐long high‐resolution model simulation run under preindustrial climate conditions, we find that the recurrence of Weddell Sea polynyas (WSPs) is mainly linked to periodic shifts of the precipitation‐rich Southern Hemisphere westerly wind belt. It is ultimately the high‐resolution ocean floor topography of the model that adds realism to the sequence of events that lead to WSPs while low‐resolution versions of the same model do not produce any open‐ocean polynyas. In this study, we propose a coupled ocean‐atmosphere mechanism to explain the periodic occurrence of polynyas. Key Points: Weddell Sea polynyas occur intermittently in a 500‐year‐long high‐resolution preindustrial Community Earth System Model simulation Periodic changes of a regional Southern Annular Mode (SAM)‐like index control the periodic changes of upper‐ocean salinity and the opening of polynyas A coupled ocean‐atmosphere mechanism is proposed to explain the periodic change of both polynya occurrence and the regional SAM‐like index